MANAGEMENT OF EARLY CHILDHOOD CHARACTER EDUCATION THROUGH THE SENLING APPROACH (CENTER AND CURRENT CIRCLE) (Case Study at Al Falah Kindergarten Cipayung East Jakarta DKI Jakarta and TK Batutis Al Ilmi Bekasi West Java) - Hanafi, Muhammad Zakaria; Ma'mun, Abin Syamsudin; Mulyanto, Agus; Sauri, R. Supyan (AGUSPATI Research Institute, 2022)
The background of the implementation of early childhood education is mostly focused on improving academic abilities only (memorization and calistung abilities) and ignoring the potential for ESQ intelligence and stimulation of Multiple Intelligences (MI). This makes the character formation of early childhood neglected. The Senling approach offers the concept of early childhood education with a fun atmosphere, not stressing and burdening children, but with the concept of directed play. Thus, children can learn optimally because the process of teaching and learning activities is adjusted to the needs, potentials and stages of early childhood development. This research is based on Jean Piaget's theory that by discovering their own knowledge through fun playing experiences, that knowledge will have strong roots in the brain, because it is integrated in the process of developing children's thinking skills that the child's character will be awakened along with life experiences received since childhood. content to adulthood. The goal is to be able to develop all ESQ and MI intelligence points in an integrated manner so that students in their learning activities are active, creative, and keep thinking by exploring their own experiences directly according to their needs and intelligence potential. ESQ and MI intelligence is what builds the foundation of early childhood character. So as to produce graduates who are competent and ready to continue their education in elementary schools as a provision for their success in the future. This dissertation research method uses a qualitative descriptive method by describing the results of research according to scientific facts through the process of observation, interviews and documentation studies. The results of the dissertation research show planning, organizing. implementation, evaluation, barriers and solutions with effective and comprehensive results, which integrate various disciplines centered on a problem, which is developed based on the needs, potential of ESQ and MI intelligence and in accordance with the stage of development. Management of early childhood character education through a sending approach prioritizes the best interests of children with the learning process carried out by placing children in a proportional position. Children are stimulated to actively carry out learning activities through directed play with the concept of happy learning so that children are able to realize the potential of ESQ and MI intelligence and produce noble characters as the basic foundation in treading early childhood success.